The role of cognitive and non-cognitive skills on labour market outcomes in Indonesia - Adhitya, Dhian; Tri Mulyaningsih; Samudro, Bhimo Rizky (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to examine the influence of cognitive and non-cognitive skills on labour market outcomes in Indonesia. The research employs the modified Mincerian model that considers the role of cognitive and personality traits of noncognitive capacities on earnings. This study relies on the data of the fifth wave Indonesian Family Life Survey (IFLS) using sample of 8,810 individuals. The IFLS was conducted in Indonesia in 2014. The research data use cross section data covering 13 provinces in Indonesia. The results show that cognitive capacities measured by schooling and noncognitive aspects of personality traits determine the labour market outcomes. Attending higher degree of education explains higher performance of labour. In addition, extraversion personality is a strong predictor of workers’ performance particularly for upper income groups. Furthermore, the contributions of marital status and personality traits are varied between male and female workers. Labour market and education policies should consider the development of both cognitive and non-cognitive skills to improve labour market outcomes.